2012
DOI: 10.1007/s10815-012-9882-z
|View full text |Cite
|
Sign up to set email alerts
|

Associations between toxic metals in follicular fluid and in vitro fertilization (IVF) outcomes

Abstract: Purpose We previously reported associations between trace concentrations of Hg, Cd and Pb in blood and urine and reproductive outcomes for women undergoing in-vitro fertilization (IVF). Here we assess measurements in single follicular fluid (FF) specimens from 46 women as a presumably more relevant marker of dose for reproductive toxicity. Methods FF specimens were analyzed for Hg, Cd and Pb using sector field-inductively coupled plasma-mass spectrometry (SF-ICP-MS). Variability sources were assessed by nested… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(31 citation statements)
references
References 45 publications
1
29
1
Order By: Relevance
“…Further, this may account for unexpected observations, possibly reflecting chance. Second, we collected FF from only a single follicle, and so previously reported follicle-to-follicle variability within woman may bias some of our results towards the null hypothesis [17]. Additionally, we did not adjust for follicle diameter, which may impact FF trace element concentrations [50].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Further, this may account for unexpected observations, possibly reflecting chance. Second, we collected FF from only a single follicle, and so previously reported follicle-to-follicle variability within woman may bias some of our results towards the null hypothesis [17]. Additionally, we did not adjust for follicle diameter, which may impact FF trace element concentrations [50].…”
Section: Discussionmentioning
confidence: 99%
“…Participant recruitment and clinical protocols were previously described in detail [16,17]. Briefly, between September 1, 2007 andAugust 31, 2008, 58 women completing a first IVF cycle at the University of California San Francisco (USCF) Center for Reproductive Health were enrolled in a prospective study to assess the impact of trace element exposures on IVF endpoints.…”
Section: Sample Selection and Clinical Protocolmentioning
confidence: 99%
See 1 more Smart Citation
“…294 Bloom et al quantified Hg, Cd and Pb in the follicular fluid surrounding the oocyte and in blood. 295 While they found a correlation for Hg and Cd concentrations in the two fluids, this was not the case for Pb. Interestingly, the Cd concentration correlated positively with fertilisation and even stronger with pregnancy.…”
Section: Elemental Analyses Of Body Tissues and Body Fluidsmentioning
confidence: 93%
“…Some authors have identified associations between trace amounts of Pb and Cd in follicular fluids from a single follicle and oocyte fertilization. An inverse association has been detected between Pb in follicular fluids and fertilization, although the association is positive for Cd (Bloom et al, 2012); furthermore, embryo fragmentation is reduced by higher blood Hg (Bloom et al, 2011).…”
Section: Direct Effects On the Ovary And Ovarian Productionmentioning
confidence: 99%